Poverty and income distribution in Latin America the story of the 1980s (Washington, D.C. World Bank, 1997)
"Highly empirical analysis documents increase in poverty and worsening of income distribution during 1980s. Demonstrates that low levels of education increase incidence of poverty and income inequality. Data provided for individual countries. Valuable data reference source"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. [275]-307).
Keywords: Income distribution -- Caribbean Area -- Statistics; Income distribution -- Latin America -- Statistics; Poverty -- Caribbean Area -- Statistics; Poverty -- Latin America -- Statistics